PORTABLE INTRUSION DETECTION AND PREVENTION SYSTEM FOR DHCP STARVATION ATTACK IN WIRELESS NETWORK - bahar, bahar (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The DHCP service has become highly critical as it plays a pivotal role in the connectivity success of approximately 22.18% of users who access the internet through wireless networks in Indonesia. DHCP services are not exempt from security threats, one of which is a Denial of Service attack known as DHCP starvation, capable of disrupting the availability of DHCP services. A novel technique employed in this attack involves manipulating the ARP protocol when the DHCP server detects IP conflicts within the network. Researchers propose an ARP protocol-based analysis method for detection and prevention, leading to the development of a portable device that serves as an Intrusion Detection and Prevention System (IDPS). This approach aims to not only enhance effectiveness but also improve efficiency. The IDPS application is crafted using the Python, with support from Scapy and Paramiko libraries. The results of detection and prevention show an accuracy rate of 100%.